APE1 and XRCC1 protein expression levels predict cancer-specific survival following radical radiotherapy in bladder cancer. - Sak, S; Harnden, P; Johnston, C; Paul, AB; Kiltie, A (2005)
INTRODUCTION: Radiotherapy offers the potential of bladder preservation in muscle-invasive bladder cancer, but only a proportion of tumors respond, and there are no accurate predictive methods. The ability of tumor cells to repair DNA damage induced by ionizing radiation influences radiosensitivity. We therefore investigated the prognostic value of the DNA repair proteins APE1 and XRCC1 in patients with muscle-invasive bladder cancer treated by radical radiotherapy. MATERIALS AND METHODS: The tumors of 90 patients with muscle-invasive transitional cell carcinoma and known clinical outcomes were immunostained with APE1 and XRCC1 antibodies. Levels of protein expression were assessed as a percentage of tumor cells with positive nuclear staining (1,000 cells per tumor). RESULTS: The median percentage of nuclear staining for APE1 was 98.7% (range, 42.2-100%) and for XRCC1 was 96.5% (range, 0.6-99.6%). High expression levels of APE1 or XRCC1 (> or = 95% positivity) were associated with improved patient cancer-specific survival (log-rank, P = 0.02 and 0.006, respectively). In a multivariate Cox regression model, APE1 and XRCC1 expression and hydronephrosis were the only independent predictors of patient survival. CONCLUSIONS: Expression levels of both APE1 and XRCC1 proteins were strongly associated with patient outcome following radiotherapy, separating patients with good outcome from the 50% with poor outcome (82% and 44%, 3-year cause-specific survival, respectively). If prospectively validated, this simple test could be incorporated into clinical practice to select patients likely to respond to radiotherapy and consider alternative forms of therapy for those unlikely to respond.